Migrant Mother - Dorothea Lange:::Creator:::::::::::: (Farm Security Administration; USA; Nipomo, California, 2022)
Migrant Mother is a photograph taken in 1936 in Nipomo, California by American photographer Dorothea Lange while she was working for the Farm Security Administration and has become an icon by many who recognize the mother's face as an emblem of the Great Depression. Lange's work is considered to be a part of the classic canon of American art and international photography and her photographs influenced the development of documentary photography and humanized the consequences of the Great Depression. A print is housed at the Museum of Modern Art in New York City. The woman has since been identified as Florence Thompson, see also photo number 0-473.